2010
DOI: 10.1111/j.1745-5871.2010.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Land Surface Temperature in Response to Land-Use/Cover Change

Abstract: In this study, we employed Geographical Information Systems and remote sensing techniques to investigate the impact of land‐use/cover change on land surface temperature (LST) in a rapidly urbanisation city, Kunming in south‐west China. Spatial patterns of LST and land use for 1992 and 2006 were derived from Landsat images to examine how LST responded to urban growth. Remote sensing indices were used to quantify land‐use types and employed as explanatory variables in LST modelling. The geographically weighted r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(70 citation statements)
references
References 31 publications
(50 reference statements)
5
65
0
Order By: Relevance
“…It can be noted that in the hot urbanized spots, the amount of mean LST is higher. Reference Zhou & Wang in 2011, (Zhou & Wang, 2011) argued that "apart from land-use change, urbanization with increased human population also contributes to the urban thermal environment change with the rising anthropogenic heat discharge." …”
Section: Resultsmentioning
confidence: 99%
“…It can be noted that in the hot urbanized spots, the amount of mean LST is higher. Reference Zhou & Wang in 2011, (Zhou & Wang, 2011) argued that "apart from land-use change, urbanization with increased human population also contributes to the urban thermal environment change with the rising anthropogenic heat discharge." …”
Section: Resultsmentioning
confidence: 99%
“…For example, Zhou and Wang [36] employed this model to investigate the local relationship between LST and land cover/use (LUC) patterns. The GWR model has also been employed to investigate non-stationary relationships between climatic factors and vegetation health [37].…”
Section: The Application Of Gwr To Model the Uhi Effectmentioning
confidence: 99%
“…Several studies showed an LST increase after forest conversion to built-up areas, agricultural land (Zhou and Wang, 2011), crop land and pasture lands (Peng et al, 2014) in China. Similar observations were reported for South American ecosystems: low vegetation such as grasslands in Argentina were warmer than tall tree vegetation (Nosetto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Surface roughness affects the transferred sensible and latent heat by regulating vertical mixing of air in the surface layer (van Leeuwen et al, 2011), thereby regulating land surface temperature (LST). Through its association with microclimate, net radiation and energy exchange (Coll et al, 2009;Sobrino et al, 2006;Voogt and Oke, 1998;Weng, 2009;Zhou and Wang, 2011), LST is a major land surface parameter, and as a climatic factor it is regarded to be a main driver of diversity gradients related to the positive relationships between temperature and species richness (Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%